Mathematical models and ANFIS for determination of diffusivity and activation energy of button mushroom thin layer drying - Maryam Karimi Motlagh; Babak Beheshti; Ali Mohammad Borghei; Mohammad Gholami Parashkoohi (Emirates Journal of Food and Agriculture)
In this research, four temperature levels of 50, 60, 70, and 80 °C with a constant airflow rate of 1 (m/s). To select an appropriate drying model, 16 thin-layer drying models and Neuro-Fuzzy Inference System (ANFIS) were used. To determine the best thin-layer mathematical model, nonlinear regression analysis was employed, utilizing indices such as R2, χ2, RMSE, and MRDM. The R software version 3.6.2 was used. The results indicated that among the mathematical models, the two-term model provided the best fit. The effective moisture diffusivity for the four temperatures ranged (3.228942E-10 to 1.065814E-09) m2/s. Significant changes of color were observed in ΔE concerning temperature. ΔE and Shrinkage increased with temperature, while SI and Hue angle values decreased with temperature.The activation energy value was 2277.341 (kJ/kg). according to the ANFIS results, the Two-term model was the most appropriate for drying the thin layer of button mushrooms, with the highest correlation coefficient (R2 = 0.999) and root mean square error (RMSE = 0.001) compared to other models.